CITRA MEREK DAN KEPUTUSAN PEMBELIAN KONSUMEN : KASUS PADA PRODUK MIE INSTAN - Gianada Mawar Dikha Laras; Egi Firmansyah (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
This study aims to explore the brand image of Indomie instant noodle product which is very legendary in Indonesia. This study also aims to determine the responses of respondents regarding their purchase decisions on Indomie brand. The respondents in this study consist of 100 people who are the consumers of Indomie. Age of respondents ranges from 15 years to 50 years in Bandung. The data in this study is the primary data obtained by disseminating questionnaires while the secondary data is derived from previous research and other sources. Analysis technique in this research is descriptive analysis. The results showed that the image of Indomie products is very good in the eyes of respondents while the purchase decision is in the category of good with cultural factors, social factors, personal factors, and psychological factors affecting respondents in decision making choose Indomie products.